Integrating Acupuncture and Yoga for Pain Management in Knee Osteoarthritis - Sureshbabu venkatasamy; Viknesh Ashokan; Yashwanth Ramesh Babu (Universidad Libre, 2024)
Background: Knee osteoarthritis (OA) is a prevalent and debilitating condition. We explore the potential of a multimodal intervention for managing knee OA, combining naturopathic therapies, acupuncture, yoga, and resistance exercise. Case description: A 68-year-old male presented with a one-year Grade II knee OA history. The patient reported moderate pain and reduced joint mobility, impacting daily activities. Clinical Findings: Initial assessment revealed a Western Ontario and McMaster University Osteoarthritis Index (WOMAC) score of 31 and a Visual Analog Scale (VAS) pain score of 5. Intervention: We provided a protocol to the patient that combined traditional naturopathic treatments, mud and mustard compresses, with evidence-based therapies, acupuncture, and resistance exercise. These modalities were chosen to address the multifaceted symptoms of knee OA, focusing on symptomatic relief and functional improvement. Results: The patient improved functional ability and decreased pain perception. WOMAC scores decreased by 26%, reflecting a notable reduction in OA severity. VAS pain scores decreased by 40%, indicating a substantial reduction in perceived pain intensity. The patient reported improved performance in daily activities, suggesting enhanced functional capacity. They also experienced weight loss and lower blood pressure, potentially contributing to overall well-being and influencing pain management and functional capabilities. Conclusions: The potential benefits of a multifaceted approach to managing knee OA were effective. The decrease in pain perception, improvements in functional ability, and even secondary outcomes like weight loss and blood pressure suggest the potential value of exploring such integrative strategies for improved patient outcomes and enhanced well-being in individuals with knee OA.